Cigarette smoking as a risk factor for coronary heart disease in women compared with men: A systematic review and meta-analysis of prospective cohort studies - Huxley, Rachel; Woodward, M. (2011)
Prevalence of smoking is increasing in women in some populations and is a risk factor for coronary heart disease. Whether smoking confers the same excess risk of coronary heart disease for women as it does for men is unknown. Therefore, we aimed to estimate the effect of smoking on coronary heart disease in women compared with men after accounting for sex differences in other major risk factors. We undertook a systematic review and meta-analysis of prospective cohort studies published between Jan 1, 1966, and Dec 31, 2010, from four online databases. We selected cohort studies that were stratified by sex with measures of relative risk (RR), and associated variability, for coronary heart disease and current smoking compared with not smoking. We pooled data with a random effects model with inverse variance weighting, and estimated RR ratios (RRRs) between men and women. We reviewed 8005 abstracts and included 26 articles with data for 3 912 809 individuals and 67 075 coronary heart disease events from 86 prospective trials. In 75 cohorts (2·4 million participants) that adjusted for cardiovascular risk factors other than coronary heart disease, the pooled adjusted female-to-male RRR of smoking compared with not smoking for coronary heart disease was 1·25 (95 CI 1·12-1·39, p<0·0001). This outcome was unchanged after adjustment for potential publication bias and there was no evidence of important between-study heterogeneity (p=0·21). The RRR increased by 2 for every additional year of study follow-up (p=0·03). In pooled data from 53 studies, there was no evidence of a sex difference in the RR between participants who had previously smoked compared with those who never had (RRR 0·96, 95 CI 0·86-1·08, p=0·53). Whether mechanisms underlying the sex difference in risk of coronary heart disease are biological or related to differences in smoking behaviour between men and women is unclear. Tobacco-control programmes should consider women, particularly in those countries where smoking among young women is increasing in prevalence.